The prerequisites for developing club abilities in rhythmic gymnastics based on the coordination requirements of the routines - Suprun A.A. ,; Terekhina R.N. ,; Ozhiganova A.S. ,; Lunina I.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to provide a scientific foundation for the development of subject skills in rhythmic gymnastics, in accordance with the coordination profile of the exercises. Methods and structure of the study. To accomplish this objective, a comprehensive evaluation of the technique for executing the fundamental elements of club activities was conducted by a panel of 15 highly skilled athletes from the Lesgaft National State University. The investigation was conducted during the preparatory phase, spanning from September to December 2024. Results and conclusions. The primary types of coordination skills for each type of technical elements with maces are identified, along with specific objectives for the development of coordination skills for each type of technical elements with maces. It is discovered that one of the objectives is to teach gymnasts to vary the height of the center of gravity of the maces when executing rotational movements for mills. Additionally, gymnasts are equipped with methodological techniques to enhance their ability to control the direction of an object's descent when performing throwing actions with two maces.